A mini-review of the effects of inhalational and intravenous anesthetics on oxidative stress in dogs - Tomsič, Katerina; Nemec Svete, Alenka (Frontiers in Veterinary Science, 2022)
General anesthesia increases the production of reactive oxygen species (ROS), which can exacerbate or increase oxidative stress and thus affect the prognosis of surgical procedures. Oxidative stress has been implicated in the development of several diseases, including cardiovascular, dermatologic, oncologic, and other diseases in dogs, as well as ischemia and reperfusion injury. Some anesthetics, such as halogenated anesthetics, have been shown to stimulate the production of ROS, while others, such as propofol, have antioxidant properties. However, the antioxidant effects of these anesthetics may not be sufficient to counteract oxidative damage at the doses used clinically. Nevertheless, the effects of anesthetics should be considered to minimize oxidative damage during anesthesia in dogs and improve the outcome of procedures requiring general anesthesia. This mini-review addresses the current knowledge on oxidative stress during inhalational and intravenous anesthesia in dogs. There is still a lack of information on the management of anesthesia in dogs with respect to oxidative stress. Further research is needed to better understand oxidative injury mechanisms and improve perioperative protocols during anesthesia in dogs.